Effects of ground flaxseed supplementation on cardiovascular disease among hemodialysis patients at a goverment hospital, in Tehran, Iran - Soltani, Saman Khalatbari (2013)
The leading cause of death in patients with chronic kidney disease including dialysis patients is cardiovascular disease (CVD). Approximately 50% of deaths in these patients are related to CVD. Among patients undergoing hemodialysis (HD), one of the major risk factors for CVD is lipid abnormalities. Besides, low level of serum albumin and high concentration of serum systemic inflammation markers, especially C-reactive protein (CRP) are important risk factors for CVD among patients undergoing HD. The present study was conducted to investigate the effects of flaxseed supplementation on cardiovascular risk factors among patients undergoing HD. This was a randomized interventional study involving 38 patients on maintenance HD (20 males, 18 females) with lipid abnormalities (Triglyceride > 2.26 mmol/L and/or high density lipoprotein-cholesterol < 1.1 mmol/L) in the age range of 23 to 77 years. Patients enrolled in the study did not have diabetes, inflammatory diseases, or infection disease, and none of them received omega-3 fatty acid supplement and lipid lowering drugs. They were randomly assigned to either a flaxseed or control group (n=19). Subjects in the flaxseed group received 40 g/d ground flaxseed for 8 weeks, whereas subjects in the control group consumed their usual diet, without any flaxseed supplementation. The outcomes of the study were evaluated at baseline, week 4 and 8. The primary outcomes were serum lipid profile, serum CRP and serum albumin levels. The secondary outcome measures were anthropometric measurements and dietary intake (assessed by 2- day record and one day food recall). In this study, serum concentrations of triglyceride (TG; p < 0.001), total cholesterol (TC; p < 0.01), and low density lipoprotein-cholesterol (LDL-C; p < 0.01) decreased significantly within the flaxseed group over time by 30%, 14% and 17%, respectively. There were significant increases in serum concentrations of TG, TC, and LDL-C within the control group by 21%, 15% and 8%, respectively. The mean changes in serum TG, TC, and LDL-C were statistically significant from baseline to week 4 (p < 0.05) and 8 (p < 0.001) between the two groups. Serum high density lipoprotein-cholesterol (HDL-C) and serum albumin increased significantly by 16% and 9%, respectively within the flaxseed group over time (p < 0.01). There was significant reduction in serum HDL-C and albumin level within the control group over time by 10% and 5%, respectively. Serum CRP concentration reduced significantly by 31% within the flaxseed group over time (p < 0.05), whereas no significant change was observed in the control group. The mean changes in serum CRP was significant difference between the two groups (p < 0.05). Baseline dietary intakes data were comparable with the exception of the control group having higher intake of dietary fiber than the flaxseed group (p < 0.05). At baseline, mean intakes of energy, protein, carbohydrate and dietary fiber in a large percentage of the subjects in both groups were lower than the recommended intakes. At week 8, subjects in the flaxseed group achieved the recommendation for energy (30.5 ± 9 kcal/ kg body weight/day), protein (1.2 ± 0.36 g/kg body weight/day) and dietary fiber (25 ± 4 g/d). In conclusion, 40 g/d flaxseed supplementation for 8 weeks improved lipid profiles and serum albumin level and reduces systemic inflammation in patients on maintenance HD with lipid abnormalities in addition to an overall dietary improvement.